Evaluation of diagnostic accuracy of dual-energy computed tomography in patients with chronic thromboembolic pulmonary hypertension compared to V/Q-SPECT and pulmonary angiogram - Schüssler, Armin; Lug, Quirin; Kremer, Nils; Harth, Sebastian; Kriechbaum, Steffen D.; Richter, Manuel J.; Guth, Stefan; Wiedenroth, Christoph B.; Tello, Khodr; Steiner, Dagmar; Seeger, Werner; Krombach, Gabriele Anja; et al. (My University, 2023)
Purpose: The relevance of dual-energy computed tomography (DECT) for the detection of chronic thromboembolic pulmonary hypertension (CTEPH) still lies behind V/Q-SPECT in current clinical guidelines. Therefore, our study aimed to assess the diagnostic accuracy of DECT compared to V/Q-SPECT with invasive pulmonary angiogram (PA) serving as the reference standard. Methods: A total of 28 patients (mean age 62.1 years ± 10.6SD; 18 women) with clinically suspected CTEPH were retrospectively included. All patients received DECT with the calculation of iodine maps, V/Q-SPECT, and PA. Results of DECT and V/Q-SPECT were compared, and the percent of agreement, concordance (utilizing Cohen's kappa), and accuracy (kappa2) to PA were calculated. Furthermore, radiation doses were analyzed and compared. Results: In total, 18 patients were diagnosed with CTEPH (mean age 62.4 years ± 11.0SD; 10 women) and 10 patients had other diseases. Compared to PA, accuracy and concordance for DECT were superior to V/Q-SPECT in all patients (88.9% vs. 81.3%; k = 0.764 vs. k = 0.607) and in CTEPH patients (82.4% vs. 70.1%; k = 0.694 vs. k = 0.560). Furthermore, the mean radiation dose was significantly lower for DECT vs. V/Q-SPECT (p = 0.0081). Conclusion: In our patient cohort, DECT is at least equivalent to V/Q-SPECT in diagnosing CTEPH and has the added advantage of significantly lower radiation doses in combination with simultaneous assessment of lung and heart morphology. Hence, DECT should be the subject of ongoing research, and if our results are further confirmed, it should be implemented in future diagnostic PH algorithms at least on par with V/Q-SPECT.
Keywords: CTEPH: chronic thromboembolic pulmonary hypertension; dual-energy CT (DECT); V/Q SPECT; iodine mapping; pulmonary angiogram; ddc:610